MENDIDIK TANPA MENGGURUI MELALUI DONGENG ANAK - Trisno Santoso; Tatik Harpawati; Nanik Prihartanti (Gelar : Jurnal Seni Budaya, 2009)
This plan tris to create a story form carried out by children. The children will fell the function of the story more real, they do not only become hears but also can use it as a developing media for their characteristics and personalities in accordance to the need, ability as well as psychology belong to children of 7 years until 12 years in elementary or intermediate school (Madrasah Iftidaiyah). This research aims to produce guie-line to tell story for children and it is hoped to be used as an effort to develop arts creativities for the elementary students. Some steps are taken to reach the target starting from observation towards learning and teaching activities in several elementary schools in Surakarta. the design of story telling guide-line is made attractively inorder hat it can raise the students’ interest to express their personal creativities in front of audiences harmoniously and structurally. For the reason, the main target is that children will be able to tell story skillfully and attractively. The forms of the plan including: (1) Buku Pedoman Tehnik Mendongeng dan Materi Cerita (The Guide-line of Story Telling Technique and Story Material; (2) Practical instructions for story telling completed with examples of stories and the performing forms to identify problems found in subject material, demonstrating instruments, the ways of conveying, and the achieve result. Other product of this research is a guide-line for story telling and its needed equiprment according to the physic and psychology belong to children of 7 years to 12 years. Based on the result, socialization is executed in order to test whether the result of the plan is surely effective, efficient, and multifunctional as a unified learning media in accordance to the children’s needs and abilities or not. Key words : story, children, personality, creativity